Public spaces, a challenge for urban renewal: case of Bardo Urban Park Project - Badr-Eddine BOUMALI; Rachid TAMINE; Abdallah LALMI; Nedjwa ELAFRI (Present Environment and Sustainable Development, 2022)
The Algerian urban renewal policy, supported by the law on urban orientation, aims to rebuild the city on itself to exploit urban wastelands. From this perspective, open spaces, wastelands, and urban interstices become major planning issues; their requalification makes it possible to ensure the economic management of space and to improve the attractiveness of the city. The results of this article are based on a case study represented by the "Modernization Plan of the Metropolis of Constantine". This new development strategy is primarily based on a program of activities centered on the rehabilitation and upgrading of central urban spaces, as well as the residential proximity of central districts, and the realization of international significant projects that would change the city's image and bring it into the modern era. Ideally, urban public places should be designed to promote unity rather than division. conviviality and community involvement among cities are significant for urban development projects.